Religious Coping, Psychological Resilience, and Academic Motivation in Islamic Educational Settings: The Moderating Roles of Parental Attachment and Islamic Values - Jayanti, Arini Mifti; Yuliasari, Hesty; Pusvitasari, Putri (Universitas Muhammadiyah Yogyakarta, 2026)
This study examined the direct effects of religious coping and psychological resilience on academic motivation. It investigated the moderating roles of parental attachment and Islamic values within an Islamic educational psychology framework. Conducted in Islamic educational settings, specifically pesantren and madrasah aliyah, in Yogyakarta, Indonesia, this study situates motivational processes at the intersection of psychological, relational, and Islamic dimensions that define the scope of Islamic educational psychology. A quantitative cross-sectional survey design was employed with a purposive sample of 305 students drawn from five Islamic educational institutions. Data were collected using five validated psychometric instruments, and analysis was conducted using hierarchical moderated multiple regression and simple slopes procedures in IBM SPSS Statistics Version 26.0 and Hayes' PROCESS macro. Results demonstrated that both religious coping and psychological resilience significantly and positively predicted academic motivation, with psychological resilience emerging as the stronger predictor. Parental attachment and Islamic values each significantly moderated both relationships, with Islamic values constituting the more dominant moderator, and the complete model explained 53.1% of the variance in academic motivation. The novelty of this study lies in its simultaneous integration of religious, psychological, and relational constructs within a unified moderation framework explicitly grounded in Islamic educational psychology, thereby extending motivational theory to a culturally and religiously underrepresented setting.